Positive environments in youth football: Perceived justice and coach feedback as predictors of athletes` needs satisfaction - Erikstad, M. K.; Haugen, T.; Hoigaard, R. (German Journal of Exercise and Sport Research, 2018)
Derived from Basic Psychological Needs Theory (BPNT) is the notion that the social environment may promote athletes` basic psychological needs, which are considered important for positive development and optimal motivational functioning. The present study investigated the predictive value of perceived justice and coach feedback on basic needs satisfaction in the context of youth football. Participants were Norwegian youth football players (N?=?532) participating in a national tournament. During the initial stage of the tournament, players completed the Coaching Feedback Questionnaire, Perceived Justice in Sport Questionnaire and Basic Psychological Needs in Exercise Scale under supervision. Regression analysis showed that perceived justice and positive/instructive coaching feedback positively predicted players` needs satisfaction, while negative feedback and non-reinforcement/ignoring mistakes were not significant predictors of needs satisfaction. Together, perceptions of justice and coach feedback explained 24% of the variance in athletes` needs satisfaction. The findings thereby indicate that athletes` perceptions of fairness and coach feedback are important in understanding youth athletes` needs satisfaction.